Evaluation of the reliability and validity of the Persian version of the Reported and Intended Behaviour Scale, a mental health stigma-related behaviour measure - Sima Garmehi; Bahareh Hakimi; Fateme Farhoudi; Ehsan Abedini (Frontiers in Psychiatry)
BackgroundSeveral instruments have been developed to measure stigma associated with mental disorders. The Reported and Intended Behaviour Scale (RIBS) is one of the validated questionnaires to assess the presence of stigma and discrimination against people with mental illness in the general population. It consists of eight items, divided into two subscales that measure reported and intended stigmatizing behaviours. This study aimed to translate and validate the RIBS in Persian.MethodsWe translated the RIBS questionnaire from English into Persian (RIBS-P) and back-translated it into English. Thereafter, ten psychiatrists evaluated its face validity. Between 2020 and 2021, 384 Persian-speaking adults (aged 18–60) residing in various cities across Iran, with internet access, participated in the study. Exploratory factor analyses were performed to determine the construct validity. The reliability of the questionnaire was assessed using internal consistency (Cronbach’s alpha coefficient) and test-retest methods.ResultsMost of the participants were 28-37 (53.9%), female (64.6%), married (51.6%), unemployed (67.7%) and educated (100%). The total Cronbach’s alpha coefficient for the RIBS-P questionnaire was high (0.732) and The test-retest results showed no significant difference. Factor analysis was used for construct validity and resulted in the extraction of one factor, the mean, standard deviation, and Cronbach’s alpha coefficient for the extracted factor were 3.25, 1.02 and 0.807. The items with the highest correlation with the extracted factor from the exploratory analysis were identified (>0.6). Age (0.00000010701), working status (0.00000010833), and education (0.00000010329) had a significant relationship with stigmatisation behaviour.ConclusionThe findings indicate that the Persian version of the RIBS is valid and reliable for assessing stigmatizing behaviours among Iranians.